The zero-mass limit problem for a relativistic spinless particle in an electromagnetic field - Ichinose, Takashi; Murayama, Taro (Proceedings of the Japan Academy Series A: Mathematical Sciences, 2014)
It is shown that mass-parameter-dependent solutions of the imaginary-time magnetic relativistic Schrödinger equations converge as functionals of Lévy processes represented by stochastic integrals of stationary Poisson point processes if mass-parameter goes to zero. © 2014 The Japan Academy.